Analisa Akuntansi Pertanggungjawaban Dan Partisipasi Anggaran Dalam Penilaian Kinerja Manajerial (Universitas Gresik, 2023)
Budget participation and accountability accounting are important elements in preparing the budget because with these two elements being effective, it will achieve the targets that have been prepared so that good performance can be achieved. In this study, the aim is to analyze more deeply about responsibility accounting and budgetary participation in improving managerial performance. The researcher uses a literature review approach, which is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research work and ideas that have been produced by researchers and practitioners. The data source used by the author is in the form of secondary data, where the researcher uses 10 articles obtained from the Google Scholar database. The results of this study indicate that changes in managerial performance are in line with changes in responsibility accounting, responsibility accounting has an important role as an evaluation and to see the financial situation in the organization, without accountability accounting everything regarding funds within the company cannot run optimally. In preparing the budget, a managerial approach is needed for its members which can reduce the performance of organizational members and participation from below so that it can be implemented effectively in related agencies.